Anomaly in Goethe’s morphology (Lebenswelt. Aesthetics and philosophy of experience., 2025)
In recent years, Goethe’s morphology has garnered renewed attention across various disciplinary fields, including the life sciences, the history of philosophy, the philosophy of science, as well as in aesthetic and theoretical domains. It is within this latter area that this article seeks to further investigate how Goethe addresses the theme of natural anomaly. By adopting a phenomenological perspective, it will be shown how anomalous cases, far from indicating a mere exception to the rule, serve as keys to accessing the nature of the Urphänomen, revealing its intrinsic indeterminateness, plasticity and temporality. In particular, the Urphänomen manifests the coexistence of formation and transformation, self-differentiation and trans-differentiation, retention of past forms and protension to new ones. Thus, in Goethean works the concept of ‘anomaly’ undergoes a semantic metamorphosis, enabling it to transcend its immediate field of application and generate theoretical implications whose potential has not yet been fully explored.